2017
DOI: 10.5194/nhess-2017-362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional rainfall thresholds for landslide occurrence using a centenary database

Abstract: Abstract. This work proposes a comprehensive methodology to assess rainfall thresholds for landslide initiation, using a centenary landslide database associated with a single centenary daily rainfall dataset. The methodology is applied to the Lisbon region and include the rainfall return period analysis that was used to identify the critical rainfall combination 10 (quantity-duration) related to each landslide event. The spatial representativeness of the reference rain gauge is evaluated and the rainfall thres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Previous investigations have shown that destruction and sliding for the majority of slope rocks are related to water effects. [17][18][19] Due to frequent rainstorms, summer rainfall concentrates in the Tonglushan ancient copper mine. The upper mine district is constitutive of intense weathering diorite porphyry having lower relative intensity and poor stability.…”
Section: Influential Factors Affecting Slope Deformationmentioning
confidence: 99%
“…Previous investigations have shown that destruction and sliding for the majority of slope rocks are related to water effects. [17][18][19] Due to frequent rainstorms, summer rainfall concentrates in the Tonglushan ancient copper mine. The upper mine district is constitutive of intense weathering diorite porphyry having lower relative intensity and poor stability.…”
Section: Influential Factors Affecting Slope Deformationmentioning
confidence: 99%
“…The ROC analysis has been frequently adopted to assess the success of binary prediction in different fields, such as medical testing (Goodenough 1974, Hanley andMcNeil 1982), machine learning (Egan 1975, Adams andHand 1999), and also landslide studies (Beguería 2006;Frattini et al 2010). In the definition of rainfall triggering thresholds, ROC curves have been recently adopted for evaluating the performance of the thresholds (Staley et al 2013;Mathew et al 2014;Gariano et al 2015;Piciullo et al 2017;Leonarduzzi et al 2017;Hong et al 2018;Vaz et al 2018), but also as a technique to identify the optimal threshold that minimise the false alarms while maximising the true alarms (e.g. correct alarms) (Postance et al 2018).…”
Section: Introductionmentioning
confidence: 99%